The War of Independence - Fiske, John, 1842-1901 (Salt Lake City, UT : Project Gutenberg, 2007)
"The War of Independence" by John Fiske is a historical account written in the late 19th century. This work offers a concise overview of the American Revolutionary War, emphasizing key events and the broader implications of the struggle for national independence. Fiske aims to clarify the complexities of this period, focusing on the causes and effects that defined the revolution rather than detailing every event. The opening of the narrative lays the groundwork for understanding the American Revolution by reflecting on celebrations commemorating important events leading up to the war. Fiske explains the importance of the period from the Declaration of Independence in 1776 to George Washington's inauguration in 1789, which marked the establishment of a new government. He highlights how approaching events, such as the undercurrents in colonial politics and the dissatisfaction with British rule, set the stage for rebellion, thus emphasizing the interconnectedness of historical occurrences leading to independence. Fiske's initial chapters are structured to draw readers into the historical context, informing them of the social, political, and economic conditions that precipitated the revolutionary fervor of the colonies. (This is an automatically generated summary.)
Release date is 2007-03-13
K.D. Thornton, Bruce Albrecht, Roger Frank and the Online Distributed Proofreading Team
Keywords: United States -- History -- Revolution, 1775-1783